Pembuatan Sirup Jahe Merah dan Pemafaatannya dalam Kesehatan - Dwita, Lusi Putri; Maifitrianti, Maifitrianti; Viviandhari, Daniek (Jurnal SOLMA, 2019)
Pengurus Pembinaan Kesejahteraan Keluarga (PKK) of Pondok Bambu, East Jakarta, was attended by members ranging in age from 30 to 70 years. There had been training on ginger planting by other parties in Pondok Bambu's RPTRA, but there was no follow-up to this activity so that the ginger plants were not well maintained. These PKK members are used to using traditional ginger medicines to maintain health, but the processing is only limited to hereditary knowledge. As educators and practitioners in the pharmaceutical field, we feel that we have an obligation to provide additional knowledge related to the proper way of treating and utilizing ginger for health. This community service activity aimed to increase the knowledge of PKK members about ginger, improve skills in processing ginger into syrup products in the hope of improving the health as well as using this knowledge to run a business in order to increase the economy of the residents. This activity was held at RPTRA Pondok Bambu Berseri using interactive and demonstration methods. The evaluation results showed an increase in knowledge of PKK members of processing ginger syrup and got the benefits of ginger for the health.